Internalisasi Nilai Moderasi Melalui Pendidikan Agama Islam di Perguruan Tinggi Umum - Purwanto, Yedi; Qowaid, Qowaid; Ma'rifataini, Lisa'diyah; Fauzi, Ridwan (Badan Litbang dan Diklat Kementerian Agama RI, 2019)
AbstractThis article describes the internalization of the value of Islamic moderation through Islamic Religious Education in the general higher education. Religious moderation, including Islam, is important to be internalized, amid the diversity of Indonesian people who have the motto of Unity in Diversity, and in the midst of the development of a dynamic environment that can damage the joints of unity because of the wrong understanding. Writing from the results of research located at the Indonesian University of Education (UPI) in Bandung uses a qualitative approach. Data collection is done through observation and interview techniques. This paper shows that the pattern of internalization of moderating values through Islamic Religious Education courses at the Indonesian Education University in Bandung. The material is adapted to student input, the competence of lecturers and subject matter support from the UPI campus environment. The curriculum is designed according to the provisions of the College. The internalization method is done through face-to-face meetings in lectures, tutorials, seminars and the like. The evaluation is done through screening Islamic insights in an orderly and written periodic report from lecturers and tutors.Abstrak Artikel ini memaparkan internalisasi nilai moderasi Islam melalui Pendidikan Agama Islam (PAI) di Perguruan Tinggi Umum (PTU). Moderasi beragama, termasuk Islam, penting untuk diinternalisasikan, di tengah kemajemukan masyarakat Indonesia yang memiliki semboyan Bhinneka Tunggal Ika, dan di tengah perkembangan lingkungan yang dinamis yang dapat merusak sendi-sendi persatuan karena adanya pemahaman yang salah. Tulisan dari hasil penelitian yang berlokasi di Universitas Pendidikan Indonesia (UPI) Bandung ini menggunakan pendekatan kualitatif. Pengumpulan data dilakukan dengan teknik observasi dan wawancara. Tulisan ini memperlihatkan bahwa pola internalisasi nilai-nilai moderasi melalui mata kuliah PAI di UPI Bandung. Materinya disesuaikan dengan input mahasiswa, kompetensi dosen pengampu mata kuliah dan dukungan dari lingkungan kampus UPI. Kurikulum yang dirancang sesuai ketentuan Perguruan Tinggi (PT). Metode internalisasi dilakukan melalui tatap muka dalam perkuliahan, tutorial, seminar dan yang semisalnya. Evaluasinya dilakukan melalui screening wawasan keislaman secara lisan dan tertulis secara laporan berkala dari dosen dan tutor.